US Foreign Policy of Chaos under Trump: the Wrecker and the Puppeteers - Pierre Guerlain (Revue LISA)
The following article assesses the changes and continuities of US foreign policy under the (apparent) leadership of the president elected in 2016, Donald Trump. It first shows the huge discrepancies between Trump’s campaign rhetoric and his actual decisions in power. It then asks the question of who formulates foreign policy and argues that Trump, lacking the necessary skills to do it himself, is open to a multiplicity of influences. The articles then discusses the areas in which Trumpism is not really challenged by authentic opponents and tackles the issue of Russiagate, which can be seen as more a domestic construction engineered by a democratic Party which refuses to analyze its role in the loss of support that led to its defeat than a bona fide international relations issue. The conclusion argues that Trump is indeed the face of US decline but not the cause of it, for this decline, linked to imperial overstretch, started a long time before his election.